THE ROLE OF JOURNALISTS IN UNCOVERING THE MURDER OF BRIGADIER JOSHUA - Eldy Haniel Rauan; Saeful Mujab; Metha Madonna (Bajang Institute, 2023)
This research aims to determine the role of journalists as part of the supervisory pillar of the authorities, in reporting on the murder case of Brigadier Joshua. Journalists play a role in providing accurate information regarding the actual situation, in this case uncovering the murder of Brigadier Joshua. So that the tangled thread of the murder case of Brigadier Joshua committed by his superiors can be revealed. To answer this problem, researchers used qualitative research methods and conducted in-depth interviews using a phenomenological approach. The results of the research show that the initial information conveyed by the Indonesian National Police (Polri) regarding the death of Brigadier Yosua gave rise to skepticism among journalists so this information was not immediately accepted. Regarding this matter, journalists stimulate the public by using diction, for example with the word